Algorithm and Software Implementation of the Diagnostic System for the Technical Condition of Powerful Units - Toirov, Olimjon; Khalikov, Salikhdjan (E3S web of conferences, 2023)
This article discusses the software implementation of the diagnostic system for auxiliary equipment of power plants (on the example of smoke exhausters). The developed program of diagnostics of auxiliary equipment of electric power plants is given on the example of condition diagnostics designed for early detection and localization of certain defects and providing recommendations for their elimination in smoke pumps, which should ensure the issuance of appropriate protocols and, upon request, protocols of the current state of smoke pumps, quality assessment of repairs and special tests, as well as graphs of retrospective parameter values for the time period selected by the user, where the users of the task - there are heads and deputy heads of workshops, senior foremen, repair engineers, as well as specialists of the planning and technical department. The problem is considered, which was solved within the framework of the software and hardware complex of the automated process control system) of the 800 MW power unit No.1 of Talimarjan TPP and is intended for operational specialists, where the task operates under the Windows operating system and the program is written in the C++ programming language Builder 6 for the development of application tasks with client -server architecture. And also the composition of the program and the program menu are given: “Task Launch”, “Daily statements”, “Input data”, “Output forms”, “Diagnostics” and “Special tests” allow you to implement the required task function at the moment. In addition, the article presents elements and components, processes and conditions of a pumping plant, pumping station and pumping station cascade, potentially dangerous and processes and conditions potentially dangerous for a pumping plant, pumping station and pumping station cascade.